Real-world data on utilization of neoadjuvant chemotherapy for muscle invasive bladder cancer: impact on surgical complications and oncological efficacy - Hege S. Haugnes; Hakon Kjaeve; Eivind Bjerkaas; Ragnhild Hellesnes; Line Hjelle; Magnus Larsen (Acta Oncologica)
Background and purpose: Recommended treatment of urothelial muscle-invasive bladder cancer (MIBC) is cisplatin-based neoadjuvant chemotherapy (NAC) followed by cystectomy, but there are challenges with low utilization of NAC. We aimed to evaluate the utilization of NAC, perioperative complications and oncological efficacy in a real-world setting.